The brazilian democracy in check (mate?): five interpretations (Research, Society and Development, 2021)
After a gradual development since its emergence in the 1980s, the democracy in Brazil has even shown signs of achieving certain consolidation. However, conflicts and imbalances between the powers of the Republic, conspiracy articulations, the return of the military to strategic positions in the Executive, and an impeachment process supported by a fragile accusation of a crime of responsibility in which the fraud was not found, among others phenomena, generated instability and put the discussion on the democratic issue in evidence. In this article, our aim is to outline a bibliographic review on the aforementioned theme, discussing the problems and limitations of post-military dictatorship Brazilian democracy based on five interpretations: Carlos Nelson Coutinho (1979), Boaventura de Souza Santos and Leonardo Avritzer (2002), Wanderley Guilherme dos Santos (2017), Luís Felipe Miguel (2017) and Vladimir Safatle, (2017). As specific objectives, we intend to apprehend a perspective on the concept of democracy, whenever possible, observing the Brazilian peculiarities; identify, from these readings, the recent problems of national policy; and, finally, to draw a panorama of the impasses of democracy in our country, that is, what makes it always on the razor's edge.